(untitled) (JURNAL ADMINISTRASI PUBLIK, 2019)
The demand that the community suaya in the village increasingly play an active role in various village development planning programs carried out by the village government starting from the planning process to decision making, until the development evaluation stage, is very clear and becomes a necessity to be implemented. Community participation in development can include forms such as; energy, thoughts, money, ideas, and opinions. From these forms of participation, in the village of Upa, Central Tobelo Subdistrict, North Halmahera Regency, the form of community participation was only in the implementation of village development, namely participation and time provided that program participation was only represented by the BPD, and public figures. in providing participation in the form of thoughts, ideas and opinions that are well made in making decisions for planning village development. The type of research used in this study is qualitative research from the methods used so it can be assessed on the efforts of the village government to increase community participation in village development in Upa village, Tobelo Tengah District, North Halmahera Regency. Village development has been done well where the community was given direction and motivation by the Head of the Village Upa to the community in the form of social motivation, as well as motivation to give enthusiasm in participating in activities in the village such as in social services in the field. In the planning of a village development program the Village Head Upa in carrying out coordination and communication tasks was carried out by holding village meetings held at the village office by inviting village representatives such as the BPD chairperson, community leaders, and village officials. This meeting was held to discuss the development programs that will be carried out in the village. The wage was given, the installation of phase I installation of street lights, rehabilitation, concrete rabbis, sirtu roads, draenase and rehap houses were not suitable for habitation. The process of community participation in village development Upa has been carried out with the stages of preparation and implementation of village development by involving community elements through their representatives. Keywords: Efforts of Village Government, Community Participation, Village Development